Analisis Analisis Penguatan Literasi dan Keaksaraan Fungsional Anak Marginal melalui Kegiatan Sanggar Anak Sungai Deli (SASUDE) - Fira Aprilia; Apryanti Situmorang; Intan Yudha Prastika; Syaukani Ali Arkan; Swarni V.M Sitanggang; Hasana Gurium (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the strengthening of literacy and functional literacy among marginalized children through the activities of the Sanggar Anak Sungai Deli (SASUDE) community in Medan City, Indonesia. Marginalized children living along the Deli River face limited access to formal education, poor economic conditions, and low literacy skills. Through a non-formal education approach, SASUDE serves as an alternative learning space that integrates basic literacy, character development, and environmental awareness. This research employs a qualitative method with data collected through observation, interviews, and documentation. The findings reveal that SASUDE plays a crucial role in improving children’s reading, writing, and functional literacy skills through creative activities, contextual learning, and personal mentoring. The main supporting factors are the dedication of volunteers and community involvement, while challenges include limited learning facilities and an unconducive environment. In conclusion, SASUDE not only enhances literacy among marginalized children but also functions as a social empowerment platform that fosters confidence, independence, and environmental awareness.